Globalization, International Education Policy and Local Policy Formation Voices from the Developing World / edited by Carolyn A. Brown. - Brown, Carolyn A.; Brown, Carolyn A. (Policy Implications of Research in Education, 2015)
This volume examines how international donor policy and funding affect local educational policy formation in developing countries and regions. Consisting of research and commentary on primary, secondary and tertiary education by scholars from developing countries around the world, it represents a seldom-heard voice. The viewpoints offered here are surprisingly varied and refreshingly divergent from much of the usual Western discourse on international educational policy formation and implementation. Starting out with an overview of the history and current condition of international donor policy, the book leaves ample room for voices from the developing world in its ten chapters that make up the second part. It concludes with a tentative discussion of theory of collaboration. The volume contributes to the global attempts at collaboration between donor and recipient countries as it presents a perspective not often heard in the clamour of voices of Western experts and local government officials.